The Effect of Hydrostatic Pressure on Enrichments of Hydrocarbon Degrading Microbes From the Gulf of Mexico Following the Deepwater Horizon Oil Spill - Marietou, Angeliki; Chastain, Roger; Beulig, Felix; Scoma, Alberto; Hazen, Terry C.; Bartlett, Douglas H. (Frontiers in Microbiology, 2018)
The Deepwater Horizon oil spill was one of the largest and deepest oil spills recorded. The wellhead was located at approximately 1500 m below the sea where low temperature and high pressure are key environmental characteristics. Using cells collected four months following the Deepwater Horizon oil spill at the Gulf of Mexico, we set up Macondo crude oil enrichments at wellhead temperature and different pressures to determine the effect of increasing depth/pressure to the in situ microbial community and their ability to degrade oil. We observed oil degradation under all pressure conditions tested (0.1, 15, and 30 megapascals [MPa]), although oil degradation profiles, cell numbers and hydrocarbon degradation gene abundances indicated greatest activity at atmospheric pressure. Under all incubations the growth of psychrophilic bacteria was promoted. Bacteria closely related to Oleispira antarctica RB-8 dominated the communities at 0.1 and 15 MPa. At 30 MPa the population appeared to shift toward Photobacterium, a genus that includes piezophiles. Alphaproteobacterial members of the Sulfitobacter, previously associated with oil-degradation, were also highly abundant at 0.1 MPa. Our results suggest that pressure acts synergistically with low temperature to slow microbial growth and thus oil degradation in deep-sea environments.